Iteratively Developing an mHealth HIV Prevention Program for Sexual Minority Adolescent Men. - Ybarra, Michele; Prescott, Tonya; Philips, Gregory; Bull, Sheana; Parsons, Jeffrey; Mustanski, Brian (AIDS & Behavior, 2016)
Five activities were implemented between November 2012 and June 2014 to develop an mHealth HIV prevention program for adolescent gay, bisexual, and queer men (AGBM): (1) focus groups to gather acceptability of the program components; (2) ongoing development of content; (3) Content Advisory Teams to confirm the tone, flow, and understandability of program content; (4) an internal team test to alpha test software functionality; and (5) a beta test to test the protocol and intervention messages. Findings suggest that AGBM preferred positive and friendly content that at the same time, did not try to sound like a peer. They deemed the number of daily text messages (i.e., 8-15 per day) to be acceptable. The Text Buddy component was well received but youth needed concrete direction about appropriate discussion topics. AGBM determined the self-safety assessment also was acceptable. Its feasible implementation in the beta test suggests that AGBM can actively self-determine their potential danger when participating in sexual health programs. Partnering with the target population in intervention development is critical to ensure that a salient final product and feasible protocol are created.